Opening and Closing the Market: Evidence from the London Stock Exchange - Ellul, Andrew; Shin, Hyun Song; Tonks, Ian (Journal of Financial and Quantitative Analysis, 2005)
Abstract We investigate the performance of call markets at the open and close using a unique natural experiment provided by the London Stock Exchange where traders can choose between a call and an off-exchange dealership system. Although the call market dominates dealers in terms of price discovery, it suffers from a high failure rate to open and close trading especially when trading conditions are difficult. The call's trading costs increase with asymmetric information, slow trading, order flow imbalances, and uncertainty. Traders' resort to use of call auctions is negatively correlated with firm size, implying that the call may not be the optimal method for opening and closing trading of medium and small sized stocks.